Atezolizumab Treatment for Progressive Multifocal Leukoencephalopathy - Nicolas Lambert; Solène Dauby; Dominique Dive; Bernard Sadzot; Pierre Maquet (Emerging Infectious Diseases, 2022)
Atezolizumab successfully reinvigorated JC virus immunity in a patient in Belgium with progressive multifocal leukoencephalopathy, as demonstrated by clinical, virologic, and radiologic response to treatment. However, the treatment also resulted in immune reconstitution inflammatory syndrome and life-threatening immune-related adverse events. These conditions were treated with corticosteroids, leading to treatment resistance.